A Novel Clinical Protocol for Placement and Management of Indwelling Urinary Catheters in Older Adults in the Emergency Department. (20th August 2015) - Mulcare, Mary R.; Rosen, Tony; Clark, Sunday; Viswanathan, Kartik; Hayes, Jaime Lynn; Stern, Michael E.; Flomenbaum, Neal E.; Heard, Kennon
Abstract Objectives Indwelling urinary catheters (IUCs) are placed frequently in older adults (age ≥ 65 years) in the emergency department (ED) and carry significant risks. The authors developed, implemented, and assessed a novel clinical protocol to assist ED providers with appropriate indications for placement, reassessment, and removal of IUCs in elders in the ED. Methods A comprehensive, evidence‐based clinical protocol was built from an extensive literature review and ED provider focus groups. It was implemented at a university‐based medical center with a 20‐minute scripted slide presentation. Written surveys were administered before, after, and at 6 months to assess providers' baseline practice and the protocol's effects. Surveys included asking providers for IUC management decisions in 25 unique clinical scenarios. Rates of IUC placement and catheter‐associated urinary tract infections (CAUTIs) were compared in ED older adult patients admitted to the hospital in the 6 months before and after protocol implementation. Results A total of 111 ED providers participated in the all three surveys. Immediately after protocol introduction, providers anticipated that this intervention would reduce rates of IUC use and increase patient safety. At 6‐month follow‐up, 81% felt the protocol had changed their practice, and 39% reported frequently referencing the protocol. In the clinical vignettes, ED providers correctly identified the appropriate approach for IUC placement in 63% of cases at baseline with an increase of 22% (95% confidence interval [CI] = 19% to 25%) postintervention and an increase of 8% (95% CI = 6% to 12%) between baseline and 6 months. An absolute reduction in the use of IUCs of 3.5% (p < 0.001) for older adults admitted to the hospital was observed after implementation of the protocol. There were three CAUTIs attributable to the ED in the 6 months prior to implementation and none in the 6 months after. Conclusions This comprehensive, evidence‐based clinical protocol was well received by participants and was associated with a sustained change in self‐reported practice, as supported by a reduction in IUC placement in admitted older adults and a reduction in CAUTIs attributable to the ED for this vulnerable population over the 6‐month study period.